Crystal structure of the CCA-adding enzyme from Arabidopsis thaliana - Xiao Wang; Yuan-Yuan Li; Zi-Yan Dou; Jia Wang; Lin Liu (Journal of Structural Biology: X)
The 3′-terminal CCA-end of tRNA is essential for the attachment of amino acids and correct positioning of the aminoacyl-tRNA in the ribosome. In higher plants, the CCA sequence is synthesized, maintained, and repaired by class-II CCA-adding enzymes encoded by a single nuclear gene but multi-targeted to the nucleus, cytoplasm, plastids, and mitochondria. The structure of plant class-II CCA-adding enzyme remains unsolved. Here we describe the crystal structure of CCA-adding enzyme from Arabidopsis thaliana (AtCCA). The overall structure of AtCCA is similar to other class-II CCA-adding enzymes, but significant differences occur in the body domain. Structural comparison of body and tail domains between AtCCA and other class-II CCA-adding enzymes unravels three specific regions of AtCCA. Based on the modeled AtCCA-tRNA complex, AtCCA may have a different tRNA binding pattern. The three specific regions located in the body domain of AtCCA also provide candidate regions for multi-targeted sorting.